2006
DOI: 10.1099/ijs.0.64043-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychrobacter cryohalolentis sp. nov. and Psychrobacter arcticus sp. nov., isolated from Siberian permafrost

Abstract: Three Gram-negative, non-motile, non-pigmented, oxidase-positive coccobacilli capable of growth at temperatures from −10 to 30 °C and salinities of 0 to 1.7 M NaCl were isolated from Siberian permafrost and characterized. Both 16S rRNA and gyrB gene sequencing studies placed the isolates in the Gammaproteobacteria within the genus Psychrobacter. However, with higher bootstrap values and reproducible tree topologies, gyrB represented a more reliable phylogenetic marker for the taxonomy of Psychrobacter species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 32 publications
5
107
1
2
Order By: Relevance
“…Psychrobacter arcticus 273-4 was isolated from Kolyma lowland permafrost sediments continuously frozen for 10,000 to 40,000 years (3,50). Siberian permafrost imposes four continuous stressors on resident microbes, including stable temperatures of approximately Ϫ10°C, desiccation due to freezing, decreased nutrient availability, and low continuous levels of radiation from soil minerals (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Psychrobacter arcticus 273-4 was isolated from Kolyma lowland permafrost sediments continuously frozen for 10,000 to 40,000 years (3,50). Siberian permafrost imposes four continuous stressors on resident microbes, including stable temperatures of approximately Ϫ10°C, desiccation due to freezing, decreased nutrient availability, and low continuous levels of radiation from soil minerals (21).…”
mentioning
confidence: 99%
“…Ponder et al showed that P. arcticus was capable of growth at temperatures below 0°C and exhibited increased proportions of unsaturated membrane fatty acids and modified substrate utilization profiles during growth at 4°C and Ϫ2.5°C (37). P. arcticus grows in an experimentally confirmed temperature range of Ϫ10°C to 28°C and in a salinity range from 10 mM to 1.3 M NaCl (3). Therefore, we consider P. arcticus 273-4 a model organism for heterotrophic growth when an organism's environment is frozen.…”
mentioning
confidence: 99%
“…It is the first description worldwide in association with hot springs. The genus Psychrobacter, a member of the class Gammaproteobacteria, is predominantly isolated from cold and/or saline environments, such as Arctic permafrost, Antarctic ice pack, estuaries, and marine fish, including Korean fermented seafood [23][24][25][26][27][28][29]. The occurrence of Psychrobacter OTUs in the amplicon library is of interest as there are no reports from hot springs all over the World.…”
Section: Resultsmentioning
confidence: 99%
“…Pure cultures of halophilic psychrophiles with optimum salinity 20 % have not yet been obtained. Psychrobacter cryohalolentis T growing at -10 o C and 10 % salinity was described by Bakermans et al, (2006). This bacterium is not a true psychrophile but rather psychrotolerant, and was isolated from the permafrost of the Kolyma Lowlands in North Siberia.…”
Section: Decomposers Of Organic Matter In Polar Environmentsmentioning
confidence: 99%
“…1.c). According to these diagrams, the prokaryotic extremophile that grows at the lowest temperature (-10 o C) and 10 % salinity currently known is the psychrotolerant mesophilic species Psychrobacter cryohalolentis, which was isolated from the permafrost of the Kolyma Lowlands of North Siberia (Bakermans et al 2006). Psychrobacter submarinus is the most halotolerant true psychrophile growing around 15 % salinity (Romanenko et al, 2002).…”
Section: Extremophiles Within Physico-chemical Matrixmentioning
confidence: 99%